Best waveform score for diagnosing keratoconus - Luz,Allan (2013)
PURPOSE: To test whether corneal hysteresis (CH) and corneal resistance factor (CRF) can discriminate between keratoconus and normal eyes and to evaluate whether the averages of two consecutive measurements perform differently from the one with the best waveform score (WS) for diagnosing keratoconus. METHODS: ORA measurements for one eye per individual were selected randomly from 53 normal patients and from 27 patients with keratoconus. Two groups were considered the average (CH-Avg, CRF-Avg) and best waveform score (CH-WS, CRF-WS) groups. The Mann-Whitney U-test was used to evaluate whether the variables had similar distributions in the Normal and Keratoconus groups. Receiver operating characteristics (ROC) curves were calculated for each parameter to assess the efficacy for diagnosing keratoconus and the same obtained for each variable were compared pairwise using the Hanley-McNeil test. RESULTS: The CH-Avg, CRF-Avg, CH-WS and CRF-WS differed significantly between the normal and keratoconus groups (p<0.001). The areas under the ROC curve (AUROC) for CH-Avg, CRF-Avg, CH-WS, and CRF-WS were 0.824, 0.873, 0.891, and 0.931, respectively. CH-WS and CRF-WS had significantly better AUROCs than CH-Avg and CRF-Avg, respectively (p=0.001 and 0.002). CONCLUSION: The analysis of the biomechanical properties of the cornea through the ORA method has proved to be an important aid in the diagnosis of keratoconus, regardless of the method used. The best waveform score (WS) measurements were superior to the average of consecutive ORA measurements for diagnosing keratoconus.